An ion beam deceleration lens for ultra-low-energy ion bombardment of naked DNA - P. Thopan (2018)
Study of low-energy ion bombardment effect on biological living materials is of significance. High-energy ion beam irradiation of biological materials such as organs and cells has no doubt biological effects. However, ion energy deposition in the ion-bombarded materials dominantly occurs in the low-energy range. To investigate effects from very-low-energy ion bombardment on biological materials, an ion beam deceleration lens is necessary for uniform ion energy lower than keV. A deceleration lens was designed and constructed based on study of the beam optics using the SIMION program. The lens consisted of six electrodes, able to focus and decelerate primary ion beam, with the last one being a long tube to obtain a parallel uniform exiting beam. The deceleration lens was installed to our 30-kV bioengineering-specialized ion beam line. The final decelerated-ion energy was measured using a simple electrostatic field to bend the beam to range from 10 eV to 1 keV controlled by the lens parameters and the primary beam condition. In a preliminary test, nitrogen ion beam at 60 eV decelerated from a primary 20-keV beam bombarded naked plasmid DNA. The original DNA supercoiled form was found to change to relaxed and linear forms, indicating single or double strand breaks. The study demonstrated that the ion bombardment with energy as low as several-tens eV was possible to break DNA strands and thus potential to cause genetic modification of biological cells. © 2013 Elsevier B.V. All rights reserved.